Air Malaysia pollution index generation by using Fuzzy Logic Air Quality Index (FLAQI) system / Mohd Fazril Izhar Mohd Idris ... [et al.] - Mohd Idris, Mohd Fazril Izhar; Mohamad Tohir, Siti Asma; Abd Aziz, Khairu Azlan (Universiti Teknologi MARA, Kedah, 2021)
Air pollution refers to the release of pollutant into th e air that is detrimental to human health and the planet. In Malaysia, air pollution index was generated by the Air Pollution Index in Malaysia (APIMS) under the Department of Environment (DOE). This study aims to analyze air pollution in Malaysia by using fuzzy logic to determine the performa nce of Fuzzy Logic Air Quality Index (FLAQI) by comparing the value with the APIMS. The method used in this system is a fuzzy logic system. This method is preferred since it is user-friendly, and the rules set up are from the hierarchical fuzzy systems. Besides, the membership of each input and output is entered in the MATLAB software to generate the output of FLAQI based on parameters (suspended specific matter of less than 25 microns in size 5, ozone, carbon monoxide, nitrogen dioxide, sulfur dioxide, and suspended particular matter of less than 10 microns) and the IF-THEN rules. 362 data have been analyzed and compared to the actual data from DOE. Therefore, the fuzzy logic approach can generate the air pollution index as it shows 82.32% of accuracy between actual data with the output of FLAQI.